PELAKSANAAN PEMENUHAN NAFKAH ANAK PASCA PERCERAIAN DI PROVINSI RIAU - Gushairi Gushairi (Fakultas Syariah dan hukum Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The primary issue in this study is the ineffectiveness and lack of implementation of the fulfillment of children's support by their biological father following the parent’s divorce in Riau Province in 2020. This study aims to determine and analyze the implementation of the fulfillment of children's support following a divorce that occurred in Riau Province in 2020, particularly obstacles in the application of court decisions in the jurisdiction of the Religious Courts in Riau Province. This study employed field research. It was conducted by going directly to the research object area to collect data on the implementation of the fulfillment of children's support following a divorce in Riau Province in 2020. The findings of this study indicate that based on the results of interviews with 55 informants, in practice, many fathers including civil servants, members of the National Police/TNI, and BUMN/private employees in Riau Province, are not responsible for providing support to their children following their divorce for various reasons. The factors that cause a father not to provide support for his child following a divorce are because he does not have a steady income, has remarried to another woman, his whereabouts are unknown, lack of communication between father and son, and is reluctant to provide child support. The following are the solutions for obtaining children's rights following a divorce: first, changes to the law regarding the filing of child support claims; second, legal awareness for child support advocates; third, improvement of the role of mediators in determining children's support following a divorce; fourth, the existence of binding rules related to the provision of child support; fifth, the establishment of an institution concerned with the payment of child support; sixth, an amendment to the law regarding changes in the amount of child support payments; and seventh, establishment of an institution concerned with the payment of child support